RESEARCH ON STEADY STATE AND DYNAMIC PERFORMANCE OF TRANSMISSION SYSTEM BASED ON SHIFT SHOCK PROBLEM - CHANG GuangBao; LI HongGeng; WANG TianXiu; LIU JieChang; HUANG YuanYi (Jixie qiangdu)
In order to solve the problem of abnormal noise when the car is shifted, the dynamic model of transmission system with 7 degrees of freedom is established. The model contains flywheel, clutch, gearbox, transmission shaft, drive shaft and tire. Using the established mathematical model, natural frequency and main vibration shape of the transmission system can be obtained. With the help of Adams software to build a multi-body dynamics model of the transmission system, and then perform modal analysis calculations on the model, the main kinetic energy that affects the shift shock is concentrated in the flywheel, and the main potential energy is concentrated in the drive half shaft. Starting from the excitation, constructing the clutch vibrationdamping characteristic model, and analyzing the sensitivity of the clutch clearance angle, it can be concluded that the larger the clearance angle, the more obvious the shift shock. Therefore, the optimized design is carried out for the flywheel inertia, drive axle stiffness, and clutch clearance angle, and is installed on the real vehicle for verification. The results show that the shift shock of the vehicle is effectively improved by installing the optimized components. The established model and analysis method have guiding significance for improving the shift shock.